Research for higher education development (1997)
The Higher Education sector is composed of all universities; colleges of education and technology and other institutes of post secondary education . It also includes all research institutes, experimental campuses and schools operating under the direct control of, or administered by, or associated with, the higher education establishments. This paper examines the quality of research in developing human resources to facilitate the development of the nation. It discusses the challenges and the role of research and higher education in support of teacher education programs and related policy processes in international context. It analyses the state-of-art in the interface between teacher education, higher education and teacher policy development. It addresses the issues related to research and education as well as their contribution to teacher education policy development processes. It explains how higher education can contribute through research and capacity building to teacher education policy development process in Nigeria. It recommends the future collaboration between the key international institutions and academics.